Effect of attending to a ball during a side-cut maneuver on lower extremity biomechanics in male and female athletes - Fedie, R.; Carlstedt, K.; Willson, J. D.; Kernozek, T. W. (Sports Biomechanics, 2010)
Many sports associated with anterior cruciate ligament (ACL) injury require athletes attend to a ball during participation. We investigated effects of attending to a ball on lower extremity mechanics during a side-cut maneuver and if these effects are consistent for males and females. Sagittal and frontal plane hip and knee kinematics and joint moments were measured during side-cut maneuvers in 19 male and 19 female National Collegiate Athletic Association division III basketball players. Participants also experienced two side-cut conditions that required attention to a ball. Our results did not indicate that the effect of attention varies with gender. However, during side-cut conditions while attending to a ball, internal knee adductor moment was 20% greater (p = 0.03) and peak knee flexion angle was 4° larger (p < 0.01). Females demonstrated 5° less hip flexion (p = 0.046), 12° less knee flexion (p < 0.01), and 4° more knee abduction (p = 0.026) at initial contact during all side-cut conditions than males. Attention to a ball may affect lower extremity mechanics relevant to ACL injury. The validity of laboratory studies of lower extremity mechanics for sports that include attention to a ball may be increased if participants are required to attend to a ball during the task.